2021
DOI: 10.1002/adsc.202100201
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Synthesis of Phloretin α‐Glucosides Using a Sucrose Phosphorylase Mutant and its Effect on Solubility, Antioxidant Properties and Skin Absorption

Abstract: Glycosylation of polyphenols may increase their aqueous solubility, stability, bioavailability and pharmacological activity. Herein, we used a mutant of sucrose phosphorylase from Thermoanaerobacterium thermosaccharolyticum engineered to accept large polyphenols (variant TtSPP_R134A) to produce phloretin glucosides. The reaction was performed using 10% (v/v) acetone as cosolvent. The selective formation of a monoglucoside or a diglucoside (53% and 73% maximum conversion percentage, respectively) can be kinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 83 publications
0
23
0
Order By: Relevance
“…Therefore, it is expected that the glycosylation of these compounds causes a worsening of their antioxidant capacity, since some of the OH of the aglycon have disappeared when the glycosidic bonds are formed [28,29]. This activity loss was also reported in the glycosides of other phenolic compounds such as phloretin [30], resveratrol [31], and gallic acid [32], as well as EGCG [14]. In this sense, using the same method of radical scavenging capacity with ABTS •+ , it has been reported that EGCG 3′-O-α-D-glucopyranoside and EGCG 7-O-α-D-glucopyranoside experimented a similar reduction of antioxidant activity The use of this multiparametric approach was successful since EGCG conversion for all novel glycosides increased approximately twofold with respect to previous nonoptimized conditions (48.8% to 90% for EGCG using BGL-1-E521G and 30% to 60% with BxTW1-E495A) [18,19].…”
Section: Effect Of Glycosylation On Egcg Antioxidant Propertiesmentioning
confidence: 81%
“…Therefore, it is expected that the glycosylation of these compounds causes a worsening of their antioxidant capacity, since some of the OH of the aglycon have disappeared when the glycosidic bonds are formed [28,29]. This activity loss was also reported in the glycosides of other phenolic compounds such as phloretin [30], resveratrol [31], and gallic acid [32], as well as EGCG [14]. In this sense, using the same method of radical scavenging capacity with ABTS •+ , it has been reported that EGCG 3′-O-α-D-glucopyranoside and EGCG 7-O-α-D-glucopyranoside experimented a similar reduction of antioxidant activity The use of this multiparametric approach was successful since EGCG conversion for all novel glycosides increased approximately twofold with respect to previous nonoptimized conditions (48.8% to 90% for EGCG using BGL-1-E521G and 30% to 60% with BxTW1-E495A) [18,19].…”
Section: Effect Of Glycosylation On Egcg Antioxidant Propertiesmentioning
confidence: 81%
“…In the present work, we have analyzed the antioxidant activity of acidic XOS containing majorly one single product (X2_MeGlcA). The selected method was the ABTS •+ radical discoloration assay adapted to 96-well plates [55]. Results were compared with those obtained with beechwood xylan and a commercially available mixture of neutral XOS.…”
Section: Antioxidant Activity Of Acidic Xosmentioning
confidence: 99%
“…In this sense, previous studies have described the glucosylation of some of the phenolic compounds tested in this work and its positive effect on their properties. For instance, the glucoside of pterostilbene was proven to improve the solubility of the original aglycone and to reduce its toxicity for several human cell lines [49], while the glucosylation of phloretin also led to a higher solubility and a lower skin penetrability, which could favor a prolonged protection of the external skin layers by cosmetic preparations [55]. Nevertheless, very few cellobiosides of phenolic compounds obtained through enzymatic synthesis can be found.…”
Section: Glycosidementioning
confidence: 99%
“…The transglycosylation capability of rXynSOS and its glycosynthase variants was evaluated by setting up reactions with different donors and acceptors. The list of acceptors studied included pNPX 2 , vanillyl alcohol, 2-hydroxybenzyl alcohol, hydroquinone, gallic acid, and rosmarinic acid, which were purchased from Sigma-Aldrich, and epigallocatechin gallate (EGCG) [73], phloretin [55], and pterostilbene [49], which were provided by Prof. Francisco J. Plou (ICP-CSIC). For the native rXynSOS, 0.1% (w/v) pNPX 2 was used as xylobiose donor together with 4.6 mg/L of the enzyme and 20 mM of the acceptors.…”
Section: Transglycosylation Assaysmentioning
confidence: 99%